Orchid flora of Gunung Ulu Semangko Forest Reserve, Selangor State Park, Malaysia - Amiri, Aqlima; Abdul Hamid, Noor Haida; Mustafa, Muskhazli; Mat Esa, Muhamad Ikhwanuddin; Besi, Edward Entalai; Hoong, Tan Sin; Sandin, Debbie; Go, Rusea (Malaysian Nature Society, 2022)
The paper reported preliminary findings on orchid diversity and abundance in Gunung Ulu Semangko, Selangor. A total of 52 orchids taxa belonging to 26 genera were opportunistically sampled from a trail in Gunung Ulu Semangko. The majority of collected species were from the subfamily Epidendroideae, with 47 species (91%). The remaining were from the subfamily Orchidoideae, with five species (9%). The results have shown that most of the species collected were epiphytic, with 42 species (81%) and only ten species (19%) were terrestrial. The orchid species diversity was H = 3.74 for Shannon’s Index and D = 0.98 for Simpson’s Index. The high D and H values were supported by a high evenness value, E = 0.80, indicating that the abundance of each species was evenly distributed without complete domination by one species. Only two species of orchids were evaluated in the IUCN Red List of Threatened Species, namely the Bulbophyllum cheiropetalum (Vulnerable) and Dendrochilum cf. gracile (Least Concern). The high orchid diversity and presence of rare species discovered in this trail highlights the importance of the comprehensive botanical study to reveal the true state of diversity and conservation assessment of orchids.